Evaluation of the potential for transmission of coronavirus disease via saliva - Ali Amiri; Pantea Moradinejad; Navid Nasrabadi; Marzieh Ghasemi Vojoodi (Universidade Estadual de Campinas, 2021)
Aim: One of the main factors that play a pivotal role in the transmission of COVID-19 from human to human is saliva; according to the subject's importance, the present study aimed to evaluate the potential of transmission via the saliva of coronavirus disease. Methods: PubMed, ISI, Embase, Scopus, Medicine have been used until September 2020 to search for articles. Therefore, EndNote X9 used to manage electronic resources. A 95% confidence interval (CI) effect size, fixed effect model, Inverse-variance methods have been calculated. The positive rate of SARS-CoV2 assessed with meta analysis. To deal with potential heterogeneity, random effects were used, and I2 showed heterogeneity. I2 values above 50% signified moderate-to-high heterogeneity. The Meta-analysis has been evaluated with Stata/MP v.16 (the fastest version of Stata) statistical software. Results: According to the study's purpose, in the initial search with keywords, 19 articles were found, the full text of 3 studies was reviewed, and finally, three studies were selected. The positive rate of SARS-CoV2 was 86% (86%; 95% CI 67 %-100%). Conclusion: saliva can be a non-invasive specimen type for diagnosis of COVID-19. Dentists should be aware that saliva plays a major role in the transmission of COVID-19 from human to human, and failure to follow prevention protocols can contaminate them.